Paths to Union Renewal: Canadian Experiences - Kumar, Pradeep; Schenk, Christopher Robert (Broadview Press, 2006)
This book focuses on the efforts and progress of union revitalization and organizing, and documents the renewal initiatives undertaken by unions in Canada. Unions, separately or in coalition with other unions or social groups, have begun to re-examine the basis of their organization and activity in the face of a harsher economic and political climate. Signs of union renewal include increased rank-and-file participation in the life of the union, increased democratic decision-making, evidence of new horizontal union structures, the development of a worker-centred societal vision, and a new emphasis on organizing both internally and externally. Paths to Union Renewal addresses a subject of considerable political and social importance about which there have been a number of debates. A key impetus for this re-examination has originated in the United States where decades-long union decline has engendered new ideas adopted by a number of unions and the national central labour body the AFL-CIO. This in turn has led to debates on renewal strategies in Western Europe and Anglo-Saxon countries from Britain to Australia. Despite this, little detailed research of the processes, structures, and implications of union renewal has been undertaken across Canada. Paths to Union Renewal fills this gap by critically examining union renewal in a variety of unions, providing a basis for informed discussion and debate on the role and place of trade unions in contemporary society. –Publisher's description
Keywords: British Columbia Federation of Labour. Organizing Institute; British Columbia Government and Service Employees Union (BCGEU); Canadian Auto Workers (CAW); Canadian Union of Public Employees (CUPE); Communications; Energy and Paperworkers Union of Canada (CEP); Community unionism; Labor Unions; Labor movement; Organizational change; United Food and Commerical Workers (UFCW); United Steelworkers (USW)